Comparison of optic disc evaluation methods in neurology emergency patients. (2nd October 2019) - Alm, Mikael; Hautala, Nina; Bloigu, Risto; Huhtakangas, Juha
Abstract : Background: The optic disc examination is critical for the diagnostics of several acute neurological disorders. However, dilation of the pupil is not recommended for neurological patients, which complicates ophthalmoscopy. Aims of the study: Present pilot study compared a portable fundus camera to an ophthalmoscope in fundus examinations of neurological emergency patients. To our knowledge, this is the first comparative study of the subject. The fundus photographs were later reviewed with an ophthalmologist. Methods: The study included 60 adults, volunteer neurological emergency patients with either headache, cerebrovascular disorder, or acute confusional state (delirium). Patients' non‐mydriatic fundus examination was conducted with an ophthalmoscope and a Smartscope Pro fundus camera. Results: Fundus photography succeeded in 56 (93%), partially succeeded in 2 (3%), and failed in 2 (3%) cases compared with ophthalmoscopy that succeeded in 35 (58%), partially succeeded in 14 (23%), and failed in 11 (18%) cases ( P < .0005). The researcher and the ophthalmologist agreed in the findings in 54 out of 58 cases (93%). In six cases (7%), the researcher had failed to detect a non‐critical ophthalmic finding. Conclusions: The neurological fundus examination by fundus camera seems to be superior to regular ophthalmoscopy in defining the critical optic disc findings in emergency patients.